Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian CV Obor Pematangsiantar - Ambo Enre; Debora Hutagalung; Henri Abdiel Simbolon; Marcella Theresia Ong (Owner : Riset dan Jurnal Akuntansi, 2020)
The development of the business world that is rapidly improving resulted in increasingly fierce competition so that various ways are done by business people to maintain and develop competitive advantage against their competitors. One of the business that also got affected by the intense competition at the moment is the building materials business in CV. Obor Pematangsiantar. Fierce competition requires the owner or manager of the CV. Obor Pematangsiantar to create a strategy that is able to compete and has an advantage so that customers decide to buy CV. Obor Pematangsiantar’s product. The purpose of this study was to determine the effect of price and quality of service on purchasing decisions on the CV. Obor Pematangsiantar both partially and simultaneously. The results showed that: (1) price has a positive effect on purchasing decisions, this is evidenced by the value of tcount> ttable (11,669> 2,026) with a significance value of 0,000 (sig ? 0.05), (2) quality of service has a positive effect on decisions purchases with tcount > ttable (21,414> 2,026) with a significance value of 0,000 (sig ? 0.05), (3) price and service quality have a positive effect on purchasing decisions, this is evidenced by the value of Fcount> Ftable (441,681> 3, 25) with a significance value of 0,000 (sig ? 0.05).